Pulmonary lymphangioleiomyomatosis (LAM) having no extra-pulmonary manifestations with chemical and mechanical pleurodesis: A case report and review of literature - Mustafa Shehzad, MD; Beenish Sabir, MBBS; Dawood Shehzad, MD; Haris Mumtaz Malik, MBBS; Anurag Jha, MBBS; Muhammad Nabeel Saddique, MBBS; Javed Iqbal, RN, Ph.D (Radiology Case Reports)
Lymphangioleiomyomatosis (LAM) is a rare, progressive lung disease characterized by abnormal smooth muscle proliferation, leading to cystic destruction of the lung parenchyma. We present the case of a female in her early 40s who presented with intermittent chest pain for 1 month. Imaging revealed left hydropneumothorax with multiple bilateral pulmonary parenchymal cysts, and a subsequent lung biopsy confirmed the diagnosis of pulmonary LAM. The patient underwent video-assisted thoracoscopic surgery (VATS) with mechanical and chemical pleurodesis. Given her stable condition, no immediate sirolimus therapy was initiated, and close follow-up with serial imaging was planned. This case highlights the diagnostic challenges of LAM, especially with low VEGF-D levels, and underscores the role of pleurodesis as a management option in select patients. Early recognition and tailored management are essential to optimize patient outcomes.